Інвестиційна привабливість України та можливі шляхи її підвищення у сучасних умовах - Кулініч, Т. В.; Мричко, М. А. (Видавництво Львівської політехніки, 2013)
Розглянуто сукупність сучасних проблем, пріоритетів та шляхів підвищення інвестиційної привабливості України. Доведена необхідність додаткової інвестиційної підтримки для розвитку базових сфер економіки і соціальної сфери нашої держави. Застосовано комплексний підхід до вивчення проблем, що заважають підвищенню інвестиційної привабливості України. Розглянуто сильні сторони нашої країни і виявленоосновні об’єкти (види економічної діяльності) для капіталовкладень. Виділено завдання і умови, а також запропонована сукупність різнопланових заходів, що загалом сприятимуть реалізації позитивних змін у збільшенні притоку інвестицій у вітчизняну економіку. Визначено сфери застосування результатів дослідження щодо покращання інвестиційного клімату, а також можливі напрямки подальшого вивчення цієї проблеми. Вивчено результати міжнародних та вітчизняних аналітичних досліджень зміни рейтингу України за рівнем її інвестиційної привабливості серед інших країн світу та проаналізовано статистичні дані щодо надходження інвестицій в країну (в її окремі види економічної діяльності). Опрацьовано досвід інших країн, узагальнено та виділено найобґрунтованіші і найдієвіші ініціативи нашого уряду щодо залучення у вітчизняну економіку додаткових капіталовкладень. The article presents the analysis of the investment attractiveness of Ukraine and foreign experience of attracting investments into the economy. Based on the research done, there are proposed approaches to improving the investment climate within the country, in particular, using international experience. A complex of existing problems, priorities and ways of improving investment attractiveness of Ukraine are considered. The necessity of additional investment support for the development of basic sectors of the economy and of social development of our country has been proved. A comprehensive approach to studying the problems that hinder the improvement of investment attractiveness of Ukraine has been applied. Strengths of our country have been considered, and the main objects (types of economic activities) for capital investments have been identified. Tasks and conditions are specified, and a set of diverse measures that will, in general, facilitate investment inflows into the national economy is proposed. The areas of applying the research results in the context of improving the investment climate as well as the possible areas of further research into the given problem are determined. Conclusions and recommendations are based on the study of the results of international and national analytical research of Ukraine’s rating changes in terms of its investment attractiveness among other countries, as well as on the analysis of statistical data on the investments entering the country’s economy (its specific fields). The experience of other countries has been studied; the most reasonable and effective initiatives of Ukrainian government on attracting additional capital investments into national economy are summarized and highlighted.
Investment attractiveness of Ukraine and possible ways to increase it in current conditions
Keywords: Україна; інвестиційна привабливість; можливі шляхи підвищення; міжнародний досвід; управління; Ukraine; investment attractiveness; possible ways; increase; international experience; management